Regional Mitral Leaflet Opening During Acute Ischemic Mitral Regurgitation - Bothe, Wolfgang (2009)
BACKGROUND AND AIM OF THE STUDY: Diastolic mitral valve (MV) opening characteristics during ischemic mitral regurgitation (IMR) are poorly characterized. The diastolic MV opening dynamics was quantified along the entire valvular coaptation line in an ovine model of acute IMR. METHODS: Ten radiopaque markers were sutured in pairs on the anterior (A(1)-E(1)) and corresponding posterior (A(2)-E(2)) leaflet edges from the anterior (A(1)/A(2)) to the posterior (E(1)/E(2)) commissure in 11 adult sheep. Immediately after surgery, 4-D marker coordinates were obtained before and during occlusion of the proximal left circumflex coronary artery. Distances between marker pairs were calculated throughout the cardiac cycle every 16.7 ms. Leaflet opening was defined as the time after end-systole (ES) when the first derivative of the distance between marker pairs was greater than a threshold value of 3 cm/s. Valve opening velocity was defined as the maximum slope of marker pair tracings. RESULTS: Hemodynamics were consistent with acute ischemia, as reflected by increased MR grade (0.5 ± 0.3 versus 2.3 ± 0.7, p <0.05), decreased contractility (dP/dt(max): 1,948 ± 598 versus 1,119 ± 293 mmHg/s, p <0.05), and slower left ventricular relaxation rate (dP/dt(min): −1,079 ± 188 versus −538 ± 147 mmHg/s, p <0.05). During ischemia, valve opening occurred earlier (A(1)/A(2): 112 ± 28 versus 83 ± 43 ms, B(1)/B(2): 105 ± 32 versus 68 ± 35 ms, C(1)/C(2): 126 ± 25 versus 74 ± 37 ms, D(1)/D(2): 114 ± 28 versus 71 ± 34 ms, E(1)/E(2): 125 ± 29 versus 105 ± 33 ms; all p <0.05) and was slower (A(1)/A(2): 16.8 ± 9.6 versus 14.2 ± 9.4 cm/s, B(1)/B(2): 40.4 ± 9.9 versus 32.2 ± 10.0 cm/s, C(1)/C(2): 59.0 ± 14.9 versus 50.4 ± 18.1 cm/s, D(1)/D(2): 34.4 ± 10.4 versus 25.5 ± 10.9 cm/s; all p <0.05), except at the posterior edge (E(1)/E(2): 13.3 ± 8.7 versus 10.6 ± 7.2 cm/s). The sequence of regional mitral leaflet separation along the line of coaptation did not change with ischemia. CONCLUSION: Acute posterolateral left ventricular ischemia causes earlier leaflet opening, probably due to a MR-related elevation in left-atrial pressure; reduces leaflet opening velocity, potentially reflecting an impaired left ventricular relaxation rate; and does not perturb the homogeneous temporal pattern of regional valve opening along the line of coaptation. Future studies will confirm whether these findings are apparent in patients with chronic IMR, and may help to refine the current strategies used to treat IMR.